Enteropathogenic E. coli stimulates effector-driven rapid caspase-4 activation in human macrophages - Goddard,P; Sanchez,Garrido J; Slater,S; Kalyan,M; Ruano,Gallego D; Marchès,O; Fernández,LÁ; Frankel,G; Shenoy,A (Cell Reports, 2019)
Microbial infections can stimulate the assembly of inflammasomes, which activate caspase-1. The gastrointestinal pathogen enteropathogenic Escherichia coli (EPEC) causes localized actin polymerization in host cells. Actin polymerization requires the binding of the bacterial adhesin intimin to Tir, which is delivered to host cells via a type 3 secretion system (T3SS). We show that EPEC induces T3SS-dependent rapid non-canonical NLRP3 inflammasome activation in human macrophages. Notably, caspase-4 activation by EPEC triggers pyroptosis and cytokine processing through the NLRP3-caspase-1 inflammasome. Mechanistically, caspase-4 activation requires the detection of LPS and EPEC-induced actin polymerization, either via Tir tyrosine phosphorylation and the phosphotyrosine-binding adaptor NCK or Tir and the NCK-mimicking effector TccP. An engineered E. coli K12 could reconstitute Tir-intimin signaling, which is necessary and sufficient for inflammasome activation, ruling out the involvement of other virulence factors. Our studies reveal a crosstalk between caspase-4 and caspase-1 that is cooperatively stimulated by LPS and effector-driven actin polymerization.